Immunomodulatory and anti-inflammatory effects of agave fructans in atopic dermatitis: gut microbiota and short-chain fatty acid implication - Rios-Carlos, Marcela; Jiménez, Mariela; Cervantes-García, Daniel; Córdova-Dávalos, Laura Elena; Verduzco, Lidia E.; Enríquez-Medrano, Francisco Javier; Fabela-Sánchez, Omar; Bermúdez-Humarán, Luis G.; Salinas, Eva (Frontiers in Immunology, 2025)
IntroductionAtopic dermatitis (AD) is a chronic inflammatory skin disorder resulting from the interplay of genetic and environmental factors, with a dysregulated type-2 immune response. The association between AD onset and intestinal dysbiosis supports research into nutritional interventions such as fermentable fibers intake. Agave-derived fructans (AFs) display prebiotic activity, modulating gut microbial communities that may positively influence immune functions. In this study, we evaluated the anti-inflammatory and immunomodulatory effects of oral AFs in a rat AD model.MethodsAD-like lesions were induced in the ear of Wistar rats by frequent application of 2,4-dinitrochlorobenzene (DNCB). AFs (0.1, 1, 5 g/kg) from Agave tequilana Weber var. azul were orally administered for 13 days. Inflammation, pruritus, gene expression of transcriptional factors of immune response, and staphylococcal colonization were evaluated in lesional skin. Cytokine expression, relative abundance of the main bacterial phyla and genera, and levels of short-chain fatty acids were analyzed in the intestinal milieu.ResultsTreatment with AFs at 0.1 g/kg significantly reduced ear thickness at 1- and 6-hours post-DNCB application. Similarly, ear edema at 1 hour was attenuated, and inhibition of the NF-κB inflammatory pathway was detected. After AFs treatment at 0.1 g/kg, serum IgE levels were normalized to those of control animals. All AFs significantly decreased dermal mast cell and eosinophil counts, as well as epidermal thickening, with greater efficacy observed at lower doses. The scratching behavior remained unchanged across groups. AFs reduced Staphylococcus aureus abundance in lesional skin and restored Staphylococcus epidermidis levels to baseline. In lesional tissue, AFs downregulated Gata3, Rorc, Il4, and Il17a mRNA expression, while promoting a regulatory immune profile in mesenteric lymph nodes, characterized by increased Foxp3, Il10, and Tgfb1 expression. Administration of AFs at 0.1 and 1 g/kg promoted fecal abundance of Bifidobacterium and cecal acetic acid concentrations, whereas doses of 1 and 5 g/kg upregulated Firmicutes, Lactobacillus, and propionic acid levels. All doses reduced Proteobacteria abundance.ConclusionAFs exhibit anti-inflammatory, immunoregulatory, and microbiota-modulatory properties in both the gut and skin compartments, in a non-linear dose-response manner. These findings suggest that the intake of AFs may contribute to the therapeutic management of AD.